Distribution Modeling for Prediction of Non-point Source Pollution - 최윤영; 이병준; 최정우 (한국수처리학회지, 22(6), 2014)
To analyze peak flow rate, sediment discharge, and nutriments in the basins, 30 and 70 cells were made in Namchun and Youngchun Dam basins, respectively, and, to subdivide the watercourse direction and slope form of the river, Nam-chun and Youngchun Dam basins were divided into 120 and 208 small grids, respectively, based on finite difference method. The result of goodness of fit test at 5% of significance level in the subject basins showed that Gumbel extreme distribution was suitable. Also, in comparison between the analysis based on HEC-HMS, which is a common method for river outflow interpretation, and the analysis of peak flow rate based on AGNPS-N, the relative error between these two models were 5.4∼6.7% in Namchun basin and 6.6∼7.7% in Youngchun Dam basin, which suggests that the peak flow rate according to the probability year was sufficiently reliable considering the difference between the two models. Prediction of water quality factors (T-P and T-N) in the event of probable precipitation by using the AGNPS-N model seems to be effective for precipitation of 50 years of less in probability years, in terms of probability frequency. In terms of application area, when the basin is large, there is no significant difference in estimates of water quality factors by using this model and the correlation is low. Therefore, caution will be needed when applying it to a large basin. KCI Citation Count: 0